2023
DOI: 10.1002/2211-5463.13546
|View full text |Cite
|
Sign up to set email alerts
|

A redox‐active HybG‐HypD scaffold complex is required for optimal ATPase activity during [NiFe]‐hydrogenase maturation in Escherichia coli

Abstract: Four Hyp proteins build a scaffold complex upon which the Fe(CN)2CO group of the [NiFe]‐cofactor of hydrogenases (Hyd) is made. Two of these Hyp proteins, the redox‐active, [4Fe‐4S]‐containing HypD protein and the HypC chaperone, form the basis of this scaffold complex. Two different scaffold complexes exist in Escherichia coli, HypCD, and the paralogous HybG‐HypD complex, both of which exhibit ATPase activity. Apart from a Rossmann fold, there is no obvious ATP‐binding site in HypD. The aim of this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 43 publications
5
17
0
Order By: Relevance
“…The HypD polypeptide in complexes isolated from the iscU single mutant and the erpA-iscA and entC-feoB double-null mutants had an additional, weak polypeptide that migrated slightly faster (∼39 kDa) than the main HypD polypeptide. This additional polypeptide has been observed previously, but with greater intensity, in HypD amino acid variants lacking a complete [4Fe-4S] cluster [22]. Western blot analyses of the same samples confirmed that the dominant polypeptide migrating at ∼39 kDa was HypD (Fig.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The HypD polypeptide in complexes isolated from the iscU single mutant and the erpA-iscA and entC-feoB double-null mutants had an additional, weak polypeptide that migrated slightly faster (∼39 kDa) than the main HypD polypeptide. This additional polypeptide has been observed previously, but with greater intensity, in HypD amino acid variants lacking a complete [4Fe-4S] cluster [22]. Western blot analyses of the same samples confirmed that the dominant polypeptide migrating at ∼39 kDa was HypD (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Because HypD has a [4Fe-4S] cluster [11], and due to the fact that the inability to introduce this cofactor into the enzyme results in its destabilisation and degradation [12, 22], it was important to determine whether native HypD levels were affected in the mutants with defective Isc machineries or iron uptake systems. Therefore, the same extracts used to determine Hyd enzyme activities were analysed by western blotting with antiserum raised against HypD (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations